PENGARUH KETANGKASAN RANTAI PASOK TERHADAP KINERJA BISNIS KEDAI KOPI DI KOTA MALANG - Anisa Aprilia; Fitrotul Laili; Putri Budi Setyowati; Riska Ayu Febriana; Kristoforus Farian Waringga; Farian Waringga (JSEP (Journal of Social and Agricultural Economics), 2021)
Nowdays, café business is rapidly growing in Indonesia. It has effect to competitiveness effect to the business. Supply chain agility is crucial to increase competitive advantage in the midst of increasingly complex business competition.The aim of this study is to analyze the impact of supply chain agility on the business performance of the coffee shop in Malang, East Java. Information on research data was obtained from 65 coffee shop managers or owners who were excavated using a questionnaire and analyzed using WrapPLS. The findings of this study are that supply chain agility has a positive and significant impact on the coffee shop business performance thus it plays a role in achieving a coffee shop competitive advantage. With supply chain agility, coffee shop businesses can maintain and increase customer satisfaction and loyalty.